Implementation of Zakat Core Principles in NU CARE LAZISNU Surabaya - Moh. Taufik Hidayah; Dony Burhan Nur Hasan (Academia Open, 2025)
General Background: Zakat, Infaq, and Sadaqah (ZIS) are foundational instruments in Islamic finance aimed at achieving social justice and reducing poverty. Specific Background: Despite Indonesia’s immense zakat potential, its realization and distribution remain suboptimal due to low public understanding and uneven governance. Knowledge Gap: Prior studies have not sufficiently analyzed how grassroots zakat institutions adopt the Zakat Core Principles (ZCP), particularly regarding transparency, efficiency, and empowerment. Aims: This study investigates the application of ZCP in the distribution of ZIS at NU CARE LAZISNU Simokerto, a local zakat management unit under Nahdlatul Ulama. Results: The findings reveal that NU CARE LAZISNU Simokerto successfully implements various ZCP aspects, including legal compliance, accountability, internal and external audits, financial transparency, professional amil training, and a dual strategy in ZIS distribution (consumptive and productive). Novelty: Unlike previous studies focusing on national institutions, this study provides an in-depth look at a grassroots-level zakat organization, highlighting its operational alignment with 18 ZCP indicators. Implications: The NU CARE LAZISNU Simokerto model illustrates how structured governance and community engagement can optimize zakat management and serve as a replicable framework for similar institutions, potentially transforming mustahik into muzakki through productive programs. Highlights: ZCP standards can be implemented effectively even at local branch levels. Professionalism and audit mechanisms ensure targeted ZIS distribution. Productive empowerment shifts mustahik toward economic self-reliance. Keywords: Zakat Core Principles, zakat governance, LAZISNU, financial transparency, productive empowerment